In Patients with Membranous Lupus Nephritis, Exostosin-Positivity and Exostosin-Negativity Represent Two Different Phenotypes - Ravindran, Aishwarya (J Am Soc Nephrol, 2021)
BACKGROUND: In patients with secondary (autoimmune) membranous nephropathy, two novel proteins, Exostosin 1 and Exostosin 2 (EXT1/EXT2), are potential disease antigens, biomarkers, or both. In this study, we validate the EXT1/EXT2 findings in a large cohort of membranous lupus nephritis. METHODS: We conducted a retrospective cohort study of patients with membranous lupus nephritis, and performed immunohistochemistry studies on the kidney biopsy specimens against EXT1 and EXT2. Clinicopathologic features and outcomes of EXT1/EXT2-positive versus EXT1/EXT2-negative patients were compared. RESULTS: Our study cohort included 374 biopsy-proven membranous lupus nephritis cases, of which 122 (32.6%) were EXT1/EXT2-positive and 252 (67.4%) were EXT1/EXT2-negative. EXT1/EXT2-positive patients were significantly younger (P=0.01), had significantly lower serum creatinine levels (P=0.02), were significantly more likely to present with proteinuria ≥3.5 g/24 h (P=0.009), and had significantly less chronicity features (glomerulosclerosis, P=0.001 or interstitial fibrosis and tubular atrophy, P<0.001) on kidney biopsy. Clinical follow-up data were available for 160 patients, of which 64 (40%) biopsy results were EXT1/EXT2-positive and 96 (60%) were EXT1/EXT2-negative. The proportion of patients with class 3/4 lupus nephritis coexisting with membranous lupus nephritis was not different between the EXT1/EXT2-positive and EXT1/EXT2-negative groups (25.0% versus 32.3%; P=0.32). The patients who were EXT1/EXT2-negative evolved to ESKD faster and more frequently compared with EXT1/EXT2-positive patients (18.8% versus 3.1%; P=0.003). CONCLUSIONS: The prevalence of EXT1/EXT2 positivity was 32.6% in our cohort of membranous lupus nephritis. Compared with EXT1/EXT2-negative membranous lupus nephritis, EXT1/EXT2-positive disease appears to represent a subgroup with favorable kidney biopsy findings with respect to chronicity indices. Cases of membranous lupus nephritis that are EXT1/EXT2-negative are more likely to progress to ESKD compared with those that are EXT1/EXT2-positive.